EFFECT OF BUDDING DATE, ROOTSTOCK, AND SCION CULTIVAR AND BUDTAKE PERCENTAGE AND VEGETATIVE GROWTH CHARACTERISTICS OF PEAR ( Pyrus communis L.) - Jassem , Najem A. (Diyala Agricultural Sciences Journal, 2011)
An experiment was conduct in private nursery in Al Gra'aet location, Baghdad- Iraq, during 2009-2010 season to investigate the effect of budding date 15/8 , 30/8 and 15/9/2009 , rootstock Pyrus calleryana and Cyndonia oblonga and two pear cultivar (Al-Zoforania and Al-Osmani) on budtake percentage and seedling , vegetative growth characteristics . Results showed that budding at 15th august give the highest percentage of budtake (88.25) compared with other dates. Budding both pear cultivar on Pyrus calleryana rootstock give significantly the higher percentage of budtake, Shoot length and diameter compared with Cyndonia oblonga where budding the tow pear cultivars on Cyndonia oblonga rootstock increased shoot number, leaf area per plant and carbohydrates percentage in shoots. scion cultivar had also significant effects on vegetative growths characteristics of seedling.